The localised density of H2O2 in the effluent of a cold atmospheric pressure plasma jet determined by continuous-wave cavity ring-down spectroscopy - Klose, S.-J.; Krös, L.; van Helden, J. H. (Frontiers in Physics, 2023)
Although the research on cold atmospheric pressure plasma jets and their applications is steadily growing, several questions remain open regarding fundamental aspects of how reactive species, such as hydrogen peroxide (H 2 O 2 ), are generated in cold atmospheric pressure plasma jets, and how the composition of reactive species can be tailored for a specific purpose. Accordingly, absolute and spatially resolved distributions of the densities of reactive species in the effluent of cold atmospheric pressure plasma jets are required. In this work, a time efficient way to determine the local distribution gas phase H 2 O 2 in the effluent of a cold atmospheric-pressure plasma jet using continuous-wave cavity ring-down spectroscopy at a wavelength of 8.12 µm is presented. By a combination of an axial scan and of several radial distributions, the localised density distribution of H 2 O 2 in the effluent of the kINPen-sci plasma jet was obtained. Therefore, the effective absorption length was determined from the evolution of the radial distributions as a function of the distance from the nozzle, which was 1.6 mm close to the nozzle of the plasma jet, and increased to approximately 5 mm at a distance of 10 mm from the nozzle. The maximum density of approximately 2 • 10 14 cm −3 was found in the centre of the effluent close to the nozzle.From the presented localised density distribution, it can be concluded that H 2 O 2 is significantly generated within the plasma zone of the plasma jet. This work presents an important step towards the understanding of formation and consumption mechanisms of biomedically relevant species in the plasma zone and the effluent of a cold atmospheric pressure plasma jet.